การสร้างแบบจำลอง และการออปติไมซ์ของระบบทำความเย็นแบบเปิดด้วยเอทิลีน - ชิตทิวา กีอำไพ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
In petrochemical industries, such as an Olefins Plant, refrigeration systems (both ethylene and propylene refrigeration systems) are included. These refrigeration systems share part of its energy to the compressor to compress vapor of the refrigcrant medium. Steam turbines, which are the major energy consumption equipment, are used to drive the compressor shafts. If we can minimize the energy consumption of the compressor-turbine, it will be very cost effective in terms of operation. This thesis focuses to find the optimum operating conditions for a 4 stage centrifugal compressor and other equipment in the ethylene refrigeration system. The goals are to reduce the compressor energy consumption, resulting in reduction of high pressure steam consumption in steam turbine. Aspen plus 9.3-1 is used to create a model and optimize the ethylene refrigeration system. First, we created an accurate model based on design data and then we tested this model with actual plant data. However. We found that it could not represent the process well enough. Therefore, we used actual plant data to perform the data reconciliation. We then used the resulting model to determine the proper operating conditions using the compressor energy consumption as our criteria for optimization. It was discovered that a combination of the Ist stage suction pressure of the compressor, the speed of the compressor, and the proper flow distribution of ethylene in the compressor could reduce the energy consumption down by 1.5 % Moreover, with low rotating speed, the need for high pressure steam would be reduced by 1.507 tons/year (an amount of 647,890 Baht/year). Case study, to verify the cost of ethylene refrigeration, are conducted by increasing the flow rate of each refrigerant level by 1 ton/hr. The most expensive (at temperature -101℃) is level one nearly 142,468 Baht/ton/year. Level two (at temperature -83℃) is cheaper, about 59,598 Baht/ton/year and level three (at temperature -65℃) is the cheapest, around 29,646 Baht/ton/year.